Work Posture Analysis of Packing Process Workers Using the Reba and Owas Method (Case Study: Tiga Hati Mutiara, Sukoharjo) - Hafidh Munawir; Isnainiyah Wardatul Jannah; Eko Setiawan (Procedia of Engineering and Life Science, 2021)
Tiga Hati Mutiara is a food industry located in Sukoharjao, Central Java. One of the activities in the production process is packaging. The posture of the workers in the packing process is to stand and bend over. The position of the worker is very dangerous if it is done repeatedly and continuously. This study aims to identify the posture and ergonomic risks of workers and provide suggestions for improving worker posture. The methods used in this research are the Rapid Entire Body Assessment (REBA) method and the Ovako Work Posture Analysis System (OWAS) method. The results of the research on the packaging process using the REBA method obtained a score of 8, which means that the level of risk is high and needs immediate improvement, while the OWAS method has a score of 4, which means that this attitude is very dangerous for the musculoskeletal system and needs immediate improvement. Improvements made are to improve the position of workers and dimensions of the table. After the improvement, the REBA score was 2 and OWAS was 1, which means that the proposed posture condition is good.